Runoff characteristics in forest plots before and after wood ash fertilization - Avelino Núñez-Delgado; Francisco Quiroga-Lago; Benedicto Soto-González (Maderas: Ciencia y Tecnología, 2011)
Spreading wood ash on forest and agricultural lands has been used for years to correct pH in acid soils and as a source of plant nutrients. However, it is necessary to enhance the knowledge of potential hazards derived from such a practise. Surface runoff pollution is one of these possible hazards. In this work we studied the quality of runoff water collected in two sloped forest plots before and after wood ash spreading, with the aim of checking potential undesirable effects of ash use. We have not found environmental pollution problems in runoff derived from the ash application zones. These results encourage further research and use of wood ash as an amendment in acid sloped forest soils.